ADOLESCENT GIRLS' THOUGHT PATTERNS ON VAGINAL DISCHARGE (FLOUR ALBUS) AT VOCATIONAL SCHOOL 1 KEPENUHAN HULU ROKAN HULU REGENCY - Wahyuni, Romy (INTERNATIONAL JOURNAL OF MIDWIFERY AND BEAUTY, 2025)
Vaginal discharge refers to vaginal secretions other than blood. It is crucial for teenagers, especially young women, to understand vaginal discharge, including its signs, symptoms, causes, and prevention. This research aimed to assess the knowledge of young women about vaginal discharge (Fluor Albus) at SMKN 1 Kepenuhan Hulu, Rokan Hulu Regency. The study employed a quantitative research method with a descriptive design and a cross-sectional approach. The sampling technique used was saturated sampling, involving 100 young women at SMKN 1 Kepenuhan Hulu. Data analysis was conducted univariately. The results showed that 38 respondents (38.0%) had good knowledge about vaginal discharge, 21 respondents (21.0%) had sufficient knowledge, and 41 respondents (41.0%) had less knowledge. It is recommended that young women enhance their knowledge about vaginal discharge. Additionally, schools should provide information resources such as books, magazines, or articles related to vaginal discharge to help young women broaden their understanding.